자유학기제 영어 수업 실태 조사와 학생 및 교사의 인식 분석 - 박한나(Park, Han-Na); 최현규(Choi, Hyun-Kyu) (영어교육연구, 2018)
This research aims to grasp the real conditions of English classes in the Free Learning Semester (FLS) and examine how teachers and students perceive the FLS. For the research, lesson and evaluation plans were collected from five schools, surveys were completed by 572 Korean 7th grade middle school students, and five middle school English teachers were interviewed. The results are as follows. First, the research confirmed that teaching, learning and evaluation were implemented successfully according to the policy purpose. Students played a leading role in classes by participating actively. They were able to recognize their achievements in the learning process. Second, most students had positive attitudes towards the policy. Some satisfaction factors were diverse teaching methods and a decrease in pressure from exams. However, there were some dissatisfaction factors: pressure caused by multiple evaluation methods, fear of adapting to learning after the FLS, and fear of a decline in academic ability. Third, some positive outcomes perceived by the teachers were that most of the students felt more interest in the subject and experienced academic success. The problems that the teachers faced were the difficulties of class preparation and evaluation, students’ resistance to change, and a decline in some students’ attitudes. KCI Citation Count: 0